LEGAL LIABILITY OF MEDICAL PERSONNEL FOR MEDICAL ACTIONS WITHOUT THE PATIENT'S CONSENT (WITHOUT INFORMED CONSENT) - Zainuddin; Irsyam Risdawati (International Journal of Society and Law, 2025)
The provision of medical procedures without patient consent or without informed consent is a crucial issue in medical practice that directly touches aspects of professional ethics and the protection of patients' human rights. In Indonesia, although regulations have explicitly regulated the importance of patient consent before medical action is taken, there are still many cases of violations that have the potential to have legal repercussions for medical personnel. Violations of the principle of informed consent not only injure the patient's right to know and decide, but can also be a form of malpractice that is physically and psychologically detrimental. This research aims to answer the question of how legal liability can be imposed on medical personnel who perform medical acts without informed consent, what is the legal basis that regulates it, and the extent to which patients' legal protection is recognized and enforced. The focus of the study is directed to juridical analysis of laws and regulations as well as studies of several concrete cases that have occurred in Indonesia. The legal liability studied includes civil, criminal, and professional aspects of medical personnel. The research methodology used is a juridical normative approach with qualitative analysis techniques. Data was obtained from literature studies on laws, court decisions, professional codes of ethics, and other relevant documents. Conceptual approaches and case approaches are used to explore how legal principles are applied in practice as well as assess the effectiveness of legal protection for patients. The results of the study show that medical personnel who perform medical actions without informed consent can be held legally accountable based on the Civil Code, the Criminal Code, and Law Number 29 of 2004 concerning Medical Practice. These actions can qualify as defaults, unlawful acts, or even criminal acts. Therefore, it is important for governments and health institutions to strengthen the implementation of regulations through socialization and strict supervision of informed consent procedures. Technical revisions are also needed in the form of derivative regulations that clarify operational standards and responsive law enforcement mechanisms.